Gorlin Syndrome in Eleven Patients - Gülen Eda Utine; Yasemin Alanay; Dilek Aktaş; Koray Boduroğlu; Mehmet Alikaşifoğlu; Ergül Tunçbilek (Galenos Yayinevi, 2017)
Aim: Gorlin syndrome is an autosomal dominant disorder characterized by cutaneous basal cell carcinomas, odontogenic keratocysts and skeletal anomalies. Predisposition to certain types of cancers is among the main features of the disease. Chromosome instability was suspected as a mechanism for cancer predisposition. However, previous studies failed to prove the presence of chromosome instability. Materials and Methods: We present 11 patients with Gorlin syndrome. Results: Six of the patients were checked for increased sister chromatid exchange and were found normal. Two other patients had concurrent chromosome anomalies. Conclusion: Evidence for chromosome instability was not found in our patients. Occurrence of chromosome instability in a subgroup of patients and mechanisms underlying cancer predisposition requires further studies for full elucidation. Hairy patches and pigmentary skin lesions are among the recently defined common features of the syndrome.